ANALISIS AUDIT BUKU KAS UMUM OLEH KAP TBW DAN EVALUASI KEPATUHAN PENCATATAN TERHADAP PERMENDAGRI NOMOR 77 TAHUN 2020 PADA PUSKESMAS K - Ferdianto, Mohammad Akbar Dwi; Habibie, Samas Adimisa Mishbah (Program Studi Akuntansi Universitas Flores, 2026)
Audit of BLUD financial management, especially in recording BKU, is a form of external supervision that aims to ensure accountability, administrative order, and compliance with applicable regulations. This study aims to analyze how the audit of the BKU at Puskesmas K was conducted by KAP TBW, and evaluate the extent to which the recording was in accordance with the provisions in Permendagri Number 77 of 2020. The study used a descriptive qualitative approach with data collection techniques in the form of observation, documentation, and interviews with external auditors. The results showed that the audit was carried out in three main stages: receiving documents, determining transaction samples, and field visits to verify supporting documents. In general, the recording in the BKU was in accordance with the provisions, but administrative deficiencies were still found, such as not including the BKU number on some receipts or other supporting documents. These deficiencies hinder the traceability of transactions and reduce the efficiency of the audit process. Therefore, improvements to the financial documentation system need to be made to improve the accountability of financial management in the BLUD environment.